Analisis Risiko Financial Distress Ditinjau dari Likuiditas, Profitabilitas, dan Leverage Perusahaan Subsektor Food and Beverage - Selyna Widyadari; Herawati, Ratna; Sumaryati, Anna; Andika, Arditya Dian (Universitas Pamulang, 2026)
This study examines the effect of liquidity, profitability, and leverage on the financial distress experienced by companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) between 2021 and 2024. Financial distress is an indication of an organization’s capacity to maintain financial stability and business sustainability amid economic fluctuations. This research employs a quantitative approach using secondary data obtained from published financial statements of the companies. The sample consist of 97 companies, selected through purposive sampling, resulting in 160 firm-year observations. Data were analyzed using multiple linear regression with the assistance of IBM SPSS Statistics Version 25. To meet the classical assumption requirements, the liquidity variable and profitability variable were transformed using SQRT and Log 10. Financial distress was measured using the Grover Score (G-Score) model. This study reveal that liquidity and profitability have a significant impact on financial distress, on the other hand leverage does not have a statistically significant effect. Higher liquidity and profitability increase the Grover Score, indicating healthier financial conditions and a lower risk of financial distress. Meanwhile, leverage remains at a manageable level, creating no substantial financial pressure. This study provides empirical evidence of the importance of cash management and profitability in mitigating the risk of financial distress in the food and beverage subsector.